EKSPLORASI SIKAP DAN PENGETAHUAN MENGENAI PENGGUNAAN TURNITIN DAN TEKNIK PARAPHRASING DALAM KONTEKS AKADEMIK - Ramdani, Zulmi; Prahastuti, Nurul Fajriyah; Prakoso, Bagus Hary (Indonesian Journal of Educational Assessment, 2019)
This study aims to explore the attitudes and knowledge possessed by an academician in making an article in accordance to the ethical code of scientific research. There were 116 participants involved in this study. The research method was carried out through two stages, the first stage is test descriptive statistics psychological description of the attitude and knowledge of subjects about the use of Turnitin and citation techniques and the second stage is conducting exploration using an open questionnaire. The results showed: the subject frequency was still very low in using this media; Â there was a linear correlation between the low intensity of use and the attitude they have in the writing process; and the use of Turnitin media and the citation techniques was important.